Zeolite-induced catalytic ozonation of p-aminobenzenesulfonic acid in a bubbling reactor. Issue 5 (26th January 2016) - Zhang, S.; Wang, D.; Fan, P.P.; Zhou, L.
Abstract: This work investigated the effect of zeolite on ozonation of p-aminobenzenesulfonic acid (PAA) as model compound. Four H + -form ZSM-5 samples (labeled as HZSM-5) with respective silica/aluminum molar ratio of 25, 50, 80, and 360 were employed for comparative study and characterized before use in terms of framework structure, crystallinity, texture, surface acidity, and morphology. In ozonation process dealing with PAA, there was no remarkable impact of HZSM-5 at pH 3.5, while for scenarios of pH 9.5, the decay rate of target contaminant largely accelerated with addition of HZSM-5 zeolite acting mainly as ozone catalyst. It was interesting to note that HZSM-5 (25) compared to other zeolite congeners performed to be more effective in catalytic ozonation for degradation and mineralization of PAA. Process analysis suggested that the weak Lewis acid sites on zeolite surface might have played major role in facilitating the consumption of hydroxyl groups (Al–OH or Si–OH) and anions (OH − ) by molecular ozone, expediting locally the progress of generation and depletion giving rise to advanced oxidation. Leaching of aluminum ion during ozonation was monitored, and results indicated that elevation of pH, in favor of zeolite-induced catalysis, could appreciably inhibit de-aluminum coupled to material stability.